(‐)‐Epigallocatechin‐3‐gallate Ameliorates Insulin Resistance and Mitochondrial Dysfunction in HepG2 Cells: Involvement of Bmal1. Issue 12 (26th October 2017) - Mi, Yashi; Qi, Guoyuan; Gao, Yuqi; Li, Runnan; Wang, Yiwen; Li, Xingyu; Huang, Shuxian; Liu, Xuebo
Abstract : Scope: Normal physiological processes require a robust biological timer called the circadian clock. Dysregulation of circadian rhythms contributes to a variety of metabolic syndrome, including obesity and insulin resistance. (‐)‐Epigallocatechin‐3‐gallate (EGCG) has been demonstrated to possess antioxidant, anti‐inflammatory, and cardioprotective bioactivities. The objective of this study was to explore whether the circadian clock is involved in the protective effect of EGCG against insulin resistance. Methods and results: The results demonstrated that EGCG reverses the relatively shallow daily oscillations of circadian clock genes transcription and protein expression induced by glucosamine in HepG2 cells. EGCG also alleviates insulin resistance by enhancing tyrosine phosphorylated levels of IRS‐1, stimulating the translocation of GLUT2, and activating PI3K/AKT as well as AMPK signaling pathways in a Bmal1‐dependent manner both in HepG2 cells and primary hepatocytes. Glucosamine‐stimulated excessive secretions of ROS and depletions of mitochondrial membrane potential were notably attenuated in EGCG co‐treated HepG2 cells, which consistent with the recovery in expression of mitochondrial respiration complexes. Conclusion: The results demonstrated that EGCG possesses a Bmal1‐dependent efficacy against insulin resistance conditions by strengthening the insulin signaling and eliminating oxidative stress, suggesting that EGCG may serve as a promising natural nutraceutical for the regulation of metabolic disorders relevant to circadian clocks. Abstract : (‐)‐Epigallocatechin‐3‐gallate (EGCG), the major catechin found in green tea (Camellia sinensis), has shown a wide variety of beneficial effects. This study evinces that EGCG in the regulation of insulin resistance and glycogen synthesis triggered by glucosamine via reprograming the circadian clock and ameliorating mitochondrial function both in HepG2 cells and primary hepatocyte.